Stimulation of mesenchymal stromal cells (MSCs) via TLR3 reveals a novel mechanism of autocrine priming. Issue 9 (15th May 2014) - Dumitru, Claudia A.; Hemeda, Hatim; Jakob, Mark; Lang, Stephan; Brandau, Sven
Abstract : Mesenchymal stem/stromal cells (MSCs) are emerging as important regulators of innate and adaptive immunity. In this context, both proinflammatory and anti‐inflammatory effects have been described for MSCs. The mechanisms mediating this functional plasticity are poorly characterized at present. Here, we investigated the inflammatory responses of MSCs isolated from human nasal mucosa (nmMSCs) upon challenge with different Toll‐like receptor (TLR) ligands. We found that TLR3 ligands induced the strongest release of both proinflammatory cytokines [interleukin (IL)‐6 and IL‐8] and type I interferon by nmMSCs compared with other TLR ligands. Notably, TLR3 ligands triggered a biphasic cytokine response, with an early peak of type I interferon at 4 h poststimulation and a late release of proinflammatory cytokines at 24 h poststimulation. While the early interferon response was subject to direct stimulation, the proinflammatory response was regulated by factors released during the early cytokine response, which subsequently enhanced sensitivity to TLR3 ligation and amplified the production of IL‐6 and IL‐8 but not that of interferon. Taken together, our findings indicate that TLR3 ligands polarize the inflammatory phenotype of MSCs in a time‐dependent manner. Thus, our study proposes a novel model that helps to explain the strikingly dichotomous functionality of MSCs in inflammation and immunoregulation.—Dumitru, C. A., Hemeda, H., Jakob, M., Lang, S., Brandau, S. Stimulation of mesenchymal stromal cells (MSCs) via TLR3 reveals a novel mechanism of autocrine priming. FASEB J. 28, 3856‐3866 (2014). www.fasebj.org